MYB/AKT3 axis is a key driver of ovarian cancer growth, aggressiveness, and chemoresistance - Kunwar Somesh Vikramdeo; Orlandric Miree; Shashi Anand; Amod Sharma; Sanjeev Kumar Srivastava; Seema Singh; Rodney P Rocconi; Ajay Pratap Singh (Journal of Ovarian Research)
Abstract Background Ovarian cancer (OC) remains the most lethal gynecologic malignancy in the United States due to its late diagnosis, aggressive nature, and poor responsiveness to existing therapies. Dissecting the molecular mechanisms and identifying molecular drivers of aggressiveness and therapy resistance is critical for devising new therapies and improving patient outcomes. Methods MYB expression was evaluated in a panel of OC cell lines by immunoblotting. Gain and loss of function studies were performed by developing stable control and forced-MYB-expressing and -silenced cell lines, respectively. Functional assays included growth kinetics, clonogenicity, cell cycle, live-dead cell measurements, and annexin-V staining, followed by flow cytometry, migration and invasion assays, and MTT assays following drug treatment. Gene expression profiling was done using the nanoString PanCancer Progression panel. Chromatin immunoprecipitation (ChIP) was performed to confirm MYB binding to the responsive gene promoter, followed by siRNA-mediated silencing to establish the intermediary role in potentiating the downstream effects. Results Low to high MYB expression was reported in all OC cell lines, with negligible expression reported in normal ovarian surface epithelial cells. MYB expression was significantly higher in aggressive (SKOV3-ip) and chemoresistant (A2780-CP) OC cell lines compared to the parental (SKOV3 and A2780) cells. Functional assays in MYB-overexpressing and -silenced OC cell lines demonstrated a role of MYB overexpression in increased cell proliferation, survival, migration, invasion, EMT, and chemoresistance. nanoString analysis and comparison of transcriptomic data of MYB-silenced SKOV3-ip and MYB-overexpressing SKOV3 cells with their respective control cells identified MYB-dependent genes. Interestingly, these target genes showed a limited overlap between cell lines, suggesting a cell-specific MYB-regulated gene regulation. AKT3 was consistently identified as a common MYB-regulated gene in multiple OC cell lines and confirmed as a direct transcriptional MYB target through confirmation of MYB binding to its promoter. Pathway analysis using the MYB-regulated transcriptomic data also identified PI3K/Akt signaling to be activated in MYB-overexpressing cells. siRNA-mediated silencing of AKT3 confirmed its role in potentiating the oncogenic actions of MYB in OC cells. Conclusion MYB/AKT3 axis drives ovarian cancer growth, aggressiveness, and chemoresistance, highlighting its potential as a therapeutic target in ovarian cancer.